DEVELOPMENT OF PINEAPPLE STEM WASTE XYLAN-5- AMINOSALICYLIC ACID PRODRUG FOR COLONIC TARGETING - Rachel Praevina Nababan, Benita
Utilization of xylan from pineapple stem waste as pharmaceutical excipient can be as a solution to minimize environmental problems caused by organic waste. Xylan, is promising as a material for colon targeting of drug due to good properties such as water-insoluble, acidic resistant, and degraded only by xylanase enzyme present in colon. 5-aminosalycylic acid (5-ASA), a golden standard drug for inflammatory bowel diseases (IBD) therapy, is rapidly absorbed from the proximal part of gastrointestinal tract (GIT) when given orally leading to failure in IBD therapy. To prevent proximal part of GIT absorption, 5-ASA was conjugated with xylan to form inactive form (prodrug). The prodrug formation consisted of 2 steps: 5- formylaminosalycylic acid formation and xylan 5-ASA conjugation using 1,1’- carbonyldiimidazole in dimethylsulfoxide and triethylamine as catalyst. Prodrug were characterized by infrared and UV-Vis spectrophotometer. The in vivo profil of 5-ASA from the prodrug and the free forms was studied in Wistar rat after oral administration. Further, the activity study of xylan-5-ASA prodrug was done in colitis rat model induced by TNBS (80 mg/kg bw) through rectal route. Five groups were applied in the activity study: negative control, positive control, 5-ASA (180 mg/kg bw/day), xylan (192.96 mg/kg bw/day), and xylan-5-ASA ester conjugates (372.96 mg/kg bw/day). Observation was conducted for 14 days and disease activity index (DAI) was evaluated during that period. After 14 consecutive days, rats were sacrificed and rat’s colon was taken for analysis including colon length, weight, histology, macroscopic injury, and inflammatory mediator observation using semiquantitative RT-PCR. Based on FTIR and UV/Vis characterizations, xylan-5-ASA prodrug was successfully synthesized. Based on DAI, only group treated with xylan-5-ASA prodrug showed significant reduction compared to control group (p<0,05). This result were confirmed by histology, colon macroscopic, and inflammatory mediators observation result. The successful colon targeting of prodrug was confirmed by in vivo data after oral administration of both free 5-ASA and xylan-5-ASA prodrug. Prodrug 5-ASA shows low systemic absorption as compared to free 5-ASA. Taken together, 5-ASA conjugated with pineapple stem waste xylan shows promising form of 5-ASA for colon targeting for IBD therapy.